Erysipelothrix rhusiopathiae isolated from gullinflicted wounds in southern right whale calves - Fiorito, Carla Daniela (2016)
Southern right whales Eubalaena australis from Peninsula Valdés, Argentina, show wounds produced by kelp gulls Larus dominicanus that feed on the whales’ dorsal skin and blubber. During the 2013 whale season, several calves were reported showing kelp gull injuries with a swollen area surrounded by rhomboid-shaped raised edges. Samples from 9 calves were taken in order to establish the etiology of these rhomboid-shaped wounds; 2 calves (one living, one dead) showed gull-inflicted injuries with rhomboid-shaped edges. Samples from the dead calf were histologically characterized by the presence of dermal congestion, suppurative dermatitis and panniculitis, necrotizing vasculitis and vascular thrombosis. Erysipelothrix rhusiopathiae was detected by culture and PCR in samples from both calves. In this study we report, for the first time to our knowledge, the isolation of E. rhusiopathiae from wounds produced by gull attacks on southern right whale calves, supplying evidence that these wounds may act as an entry route for pathogens. This work provides new information about the consequences of gull-inflicted injuries for whale health.